Public and/or private? remedies against the different decisions on social care services in Hungary - Hoffman, István (Central European Public Administration Review, 2024)
Purpose: The paper examines the multi-layered remedy system in social care services in Hungary. It first analyses remedies related to the obligation of public service provision, especially remedies against normative tools for public service provision (such as decrees on fees and service standards) and the omission of duties by public bodies obliged to perform these services. A secondary focus is on remedies against the decisions and omissions by service provider institutions. Design and Approach: Hungarian legislation interprets social care services as legal relationships governed by private law with partial public law regulation. The public remedy against the decisions of the service providers is complaints, which are governed by sector-specific (public) regulations. The research examines the remedy system using legal study methods based on dogmatic analysis and involves an examination of judicial practice, namely Hungarian courts decisions on major public law remedies. Findings: Based on dogmatic and empirical analysis, the study reveals that Hungarian judicial practice has interpreted public law remedies, specifically complaints, in various ways. Following an amendment of legal regulation, the civil law-based interpretation now prevails. Although this practice has been consolidated, tensions can be observed, especially in the case of omissions. Practical implications: The paper suggests a legislative solution to mitigate these tensions, recommending that decisions establishing social care services be formalised as public decisions. Originality: The paper is based on a dogmatic analysis of the social care remedy system and, as a new element, contains an in-depth analysis of the Hungarian judicial practice on this issue.
Keywords: administrative law; Hungary; javno pravo; litigation; Madžarska; pravna sredstva; private law; public law; remedies; social care services; sodni postopek; storitve socialnega varstva; upravno pravo; zasebno pravo